16S rRNA Gene Sequencing Reveals a Shift in the Microbiota of Diaphorina citri During the Psyllid Life Cycle - Meng, Lixue; Li, Xiaoyang; Cheng, Xiaoqin; Zhang, Hongyu (Frontiers in Microbiology, 2019)
The Asian citrus psyllid (Diaphorina citri) is a major pest of citrus trees as it transmits Candidatus Liberibacter asiaticus (CLas). The composition of a host’s microbiota can affect the evolution and ecological distribution of the host. This study monitored the compositional shifts in the citrus psyllid microbiota through all the life stages (egg, nymph 1–5 stages, and adult) by next-generation sequencing and quantitative real-time PCR. There were clear differences in both α- and β-diversity of microbiota through the psyllid life stages. Microbiota diversity was markedly higher in nymph 2–5 stages than in the adult, egg, and nymph 1 stages. Proteobacteria were dominant in all the life stages of D. citri, representing > 97.5% of the total bacterial community, and Candidatus Profftella armature was the dominant genus in all the life stages. Data from the qPCR analysis showed an exponential increase in the populations of three D. citri endosymbionts: Candidatus Profftella armature, Candidatus Carsonella ruddii, and Wolbachia. The gut bacterium Pantoea was present in all the life stages, but it was markedly higher in the nymph 2-5 stages. The microbiota composition substantially differed among the egg–nymph 1, nymphs 2–5, and adult stages. Therefore, we successfully characterized the microbiota dynamics and thus identified a microbiota shift during the life cycle of D. citri by 16S rRNA gene sequencing and quantitative PCR. Moreover, 16S rRNA gene sequencing suggested that D. citri acquired the ability to bear CLas at the nymph 1 stage. This study enhances our understanding of microbial establishment in the developing D. citri and provides a reference resource for the identification of potential biocontrol approaches against this pest.